Prevalence of Tongue Normal Variant Lesions in Geriatric Patients with Hypertension in Surabaya: A Multicenter Observational Study - Parmadiati, Adiastuti Endah; Mahdani, Fatma Yasmin; Ernawati, Diah Savitri; Ayuningtyas, Nurina Febriyanti; Surboyo, Meircurius Dwi Condro; Pratiwi, Aulya Setyo; Marsetyo, Riyan Iman; Inastu, Candrika Ramya; Erawati, Vint; Fitri, Adinda Ratna (Journal of Health and Allied Sciences NU, 2023)
Introduction The risk of degenerative diseases in the elderly is higher due to aging and decreased body function. This process affects both systemic conditions and locally in the oral cavity. Aside from aging, degenerative disease itself can trigger the incidence of soft tissue abnormalities. Aging can cause structural and functional changes in the systemic vasculature, resulting in a degenerative disease such as hypertension. Elderly who suffers from hypertension can develop oral mucosa abnormalities and most of them are found on the tongue. This study was aimed to identify the prevalence of normal variant lesions on the tongue in the elderly with hypertension.Methods This was an observational descriptive study with a cross-sectional design done in January–March 2020. Samples were elderly obtained from several public health centers in Surabaya that matched the inclusion criteria. Subjective and clinical examinations were performed by oral medicine residents and specialists.Results A total of 401 elderly were screened and 147 elderly (36.65%) met the inclusion criteria which are having hypertension and willing to participate in this study. Those who met the criteria, mainly were female from the 60 to 74 years old age group. Normal variants of tongue obtained from the examination were fissured tongue (90.48%), coated tongue (63.95%), crenated tongue (33.33%), lingual varices (12.24%), and benign migratory glossitis (4.08%).Conclusion From this study, we figured out that fissured tongue was the most common normal variant lesion of the tongue in the elderly with hypertension. Coexistence between hypertension and tongue lesions can be developed from pathological changes of disease or as side effects of medication taken such as antihypertensive drugs.
Keywords: tongue; normal variants; geriatric; hypertension; oral medicine